The relationship between perceptions of organizational politics (POPS), political skills, perceived organizational support (POS), and work life balance with turnover intention - Noordina, Hassim (2013)
The study was conducted to investigate either there is a different between individual who have intention to leave the organization with individual who do not have the intention in terms of perceptions of organizational politics (POPs), political skills, perceived organizational support (POS), and work life balance. Sample for the study were 256 employees from after sales service division in one automotive company in Malaysia. Hypotheses were tested using t-test analysis. There is a significance difference between individual who have the intention to leave with individual who do not have the intention in terms of perceptions of organizational politics, political skills, and work life balance. There is also an increase or present that respondents been rating the likelihood that they would search for a new job from different profession within the next year